Denmark : Financial Sector Assessment Program-Detailed Assessment of the Core Principles for Systemically Important Payment Systems. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Detailed Assessment of the Core Principles for Systemically Important Payment Systems for Denmark. The main counterparties for the assessment were Danmarks Nationalbank and the Danish Financial Supervisory Authority Finanstilsynet. The assessment recommends that the system should have a well-founded legal basis under all relevant jurisdictions. The system's rules and procedures should enable participants to have a clear understanding of the system's impact on each of the financial risks they incur through participation in it.